PRESENSI SISWA BERBASIS RFID TERINTEGRASI WEB DENGAN NOTIFKASI BOT TELEGRAM - Mulya Kurnia Kasanova; Eddy Nurraharjo; Zuly Budiarso; Mardi Siswo Utomo (LPPM STMIK Lombok, 2021)
Until now, almost all educational institutions still use paper and pens in recording student attendance at school. This causes students to often be absent and also play truant in teaching and learning activities. The purpose of this research is to create a presence system using touchless technology, namely RFID (Radio Frequency Identification) and the use of chat bots. This technology will later go for the role of paper and pen to record the attendance of students and teachers to make it easier for admins to report to related parties and parents of students do not have to worry about the position of their children at school or not because the telegram bot monitors it from the start to the end. The results show that the system can control the attendance process in schools and can make reports correctly. This presence system will be integrated using the web which will be linked to notifications using a telegram bot. Keywords : Student attendance, Touchless Technology, RFID, Telegram Bot, Web.